Management and welfare of working equids in the Guerrero state - Robledo Reyes, Eduardo Ezequiel; Gil, Mariano Hernandez; Rojas Hernández, Saúl; Camacho Diaz, Luis Miguel; Cipriano Salazar, Moises; Villa Mancera, Abel; Olivares Pérez, Jaime (Ecosistemas y Recursos Agropecuarios, 2020)
The management of farm work equids in Guerrero, Mexico was described and related to animal welfare. Sixty-four equids owners were randomly surveyed. Horses were used more than donkeys and mules. The 89% of owners worked the animals before 5 years of age. Only 5% provide helmet management. The 83% of breeders provide living space >4 m2 . In 53% of the units animals socialize. The 45% of breeders feed on forage and grain. The 59% of breeders give access to water 2-4 portions / day and 41% ad libitum. Deworming is partial (44%) and not vaccine is applied. The common diseases are skin lesions (84%), digestive system disorders (77%), respiratory (59%) and locomotor (44%). In conclusion, the management of equids compromises their well-being in different ways, reducing their quality of life.